On the finding of the Indo-Pacific fish Scomberomorus commerson in Rhodes (Greece) - CORSINI-FOKA, M.; KALOGIROU, S. (Mediterranean Marine Science, 2008)
The occurrence of the Indo-Pacific fish Scomberomorus commerson was observed for the first time in the Hellenic waters of the SE Aegean Sea during the spring 2008. The record may represent a first indication of a population expansion of this alien species along the southern coasts of the Aegean Sea.